Sarcomatoid carcinoma in the sinonasal cavity: A retrospective case series from a single institution. Issue 5 (October 2022) - Zhu, Zhenzhen; Wang, Lei; Wang, Weiqing; Zha, Yang; Wang, Xiaowei; Han, Jinbo; Lv, Wei
Abstract: Objectives: Sarcomatoid carcinoma (SC) is rare in the sinonasal cavity with poor prognosis. This study aimed to summarize the clinical characteristics, treatment and prognosis of patients with sinonasal SC from a single tertiary medical center. Methods: Retrospective review of the clinical data of seven patients diagnosed with sinonasal SC from May 1988 to February 2021. Results: Seven patients with SC in nasal cavity and paranasal sinus, including six males and one female, aged 34-77 years (mean, 58.3 years), were included in this case series. The common presenting symptoms included epistaxis and nasal obstruction. The tumor usually occurred in nasal cavity, maxillary sinus and ethmoid sinus. Most patients were diagnosed at advanced stages with the involvement of orbit and skull base. Open and endoscopic surgery were performed in five and two patients, respectively. The follow-up period ranged from 3 to 26 months. Four patients died of disease within one year, though two received adjuvant chemotherapy and one received radiotherapy. Two patients survived without recurrence at the end of follow-up, both of them underwent adjuvant radiotherapy. One patient received palliative re-irradiation due to local recurrence of the tumor three months after the surgery, however, this patient was lost to follow-up. Conclusions: Sinonasal SC is a rare entity with an aggressive behavior and poor prognosis. Early diagnosis and multimodality treatment are recommended to improve the survival.